Exploring the Role of Neo-Humanism and Local Cultural Values in Digital English Language Learning for Elementary School Students - Ida Bagus Nyoman Mantra; I Made Suyasa; I Nyoman Adi Susrawan; Ni Wayan Adi Priantini; Ida Ayu Praba Iswari Dewi; I Kadek Dian Satriawan (Social Science Academic, 2026)
The rapid development of digital technology into English language teaching has provided new means for interactive learning, but has also raised concerns about safeguarding learners' cultural identity and promoting all-round development. This research aims to investigate the impact of neo-humanistic teachings and local cultural values to the digital English language learning of primary school students. This research was conducted through a qualitative case study approach in public and private primary schools in Bali. The data were collected by semi-structured interviews, classroom observation and document study. The study revealed five main themes: (1) incorporating local culture into English education through traditional ceremonies, folklore, arts, and environmental contexts; (2) incorporating neo-humanistic values such as empathy, cooperation, respect, responsibility, and environmental awareness into classroom activities; (3) effective use of digital technologies; (4) students' holistic development to enhance language confidence, creativity, collaboration, critical thinking, and cultural identity; and (5) implementation challenges related to digital infrastructure, culturally relevant teaching resources, and teacher readiness. This research shows that the integration of neo-humanistic principles and local knowledge turns digital English language teaching into a full learning experience beyond the simple mastery of the language. The results have practical implications for educators, curriculum developers and policy makers interested in designing culturally responsive and technology-enhanced English language teaching in elementary education.